THE EFFECT OF INQUIRY-BASED VIRTUAL LABORATORY ON STUDENTS' SCIENCE PROCESS SKILLS - Ana Rato, Antonius Umbu; Herdiawan, Akmal Arif; Wilujeng, Insih; Nurohman, Sabar; Rahmawati, Laifa; Natadiwijaya, Ismail Fikri (JURNAL EDUSCIENCE, 2024)
Science education at the junior high school level requires an approach that maximally develops students' science process skills (SPS). One way to achieve this is by utilizing interactive learning media, such as virtual laboratories, combined with an inquiry-based learning model. This study aims to determine the effect of implementing an inquiry-based virtual laboratory on improving students' SPS. The method used in this study is pre-experimental with a one-group pretest-posttest design. The subjects in this study were 32 students from class VIII D at SMP Negeri 4 Yogyakarta. Data collection was carried out by administering a pretest before treatment and a posttest after treatment. The data obtained were analyzed using paired t-test and N-Gain test. The paired t-test results showed a significance value (2-tailed) = (0.00) < 0.05, indicating the effect of the treatment on students' SPS. The N-Gain result was 0.73 in the high category, so it can be concluded that applying virtual laboratory media with the inquiry-based learning model in the inclined plane topic can enhance students' SPS in science subjects.